1982 : greatest geek year ever! [videorecording (DVD)] - Altman, Mark A.; Winkler, Henry, 1945-; Howard, Ron, 1954-; Shatner, William (2023)
An epic documentary spotlighting the pop culture milestones of 1982 including notable motion pictures, TV, music and video games of that seminal year.